Can participation in agricultural programmes improve youth agribusiness performance? Insights from the Enable Programme in East Africa - Adeyanju, Dolapo; Ejima, Joseph; Balana, Bedru; Mburu, John (International Association of Agricultural Economists, 2024)
This study addresses the gap in understanding the impact of agribusiness empowerment programmes on youth business performance in developing countries, taking the case of the ENABLE-TAAT programme in Kenya and Uganda. A multistage sampling technique was used in obtaining primary agribusiness-level data from a sample of 1003 young agripreneurs from the study countries. An Endogenous Treatment Effect Regression (ETER) model was used to identify factors influencing programme participation and impact on youth agribusiness performance. Results show that marital status, agribusiness experience, asset value, credit access, residence, prior programme awareness, and perception were the key determinants of participation. The ETER results chow that participation in the programme significantly increased youth’s agribusiness income by 7 percent and food security by 76 percent, with participants having higher asset value than non-participants. Based on these findings, we suggest policy interventions or programmes focusing on youth agribusiness empowerment, particularly those that target young actors along different agricultural value chains. We also suggest interventions geared towards mitigating constraints to credit access by young agripreneurs to ease barriers to working capital and business innovation. To increase access and participation, we recommend strategies to improve youth perception and raise awareness of these programmes.